Fennel seed powder supplementation in dairy goat diet: effects on milk productive traits, fatty acid profile and gene expression - Iommelli, Piera; Tufarelli, Vincenzo; Ceci, Edmondo; Bozzo, Giancarlo; Sarubbi, Fiorella; Ferrara, Maria; Infascelli, Federico; Tudisco, Raffaella (Frontiers in Animal Science, 2025)
The aim of the present study was to evaluate the effect of dietary supplementation with fennel seeds powder (FSP) on dairy goats. Twenty goats, homogeneous in terms of body weight (BW), days in milk (DIM), daily milk yield (DMY), and parity, were randomly assigned into two groups (CON: control; FEN: fennel). Both groups were fed alfalfa hay and corn in the barn, with the treated group (FEN) receiving an additional 15 g/head/day of FSP. From findings, no significant differences were detected in milk yield or milk chemical composition, although some fatty acids showed variations between the groups. Additionally, a gene expression analysis was conducted on candidate genes related to milk production, lipid metabolism and the antioxidant system without revealing any differences. However, this field of research appears promising, and further studies are needed to standardize the optimal dosage to achieve positive effects on yield and genomic activation.